Analisis Pengaruh Pemberian Kompensasi Finansial dan Non Finansial Terhadap Kinerja Karyawan (Pada karyawan PT Astra International,Tbk-Daihatsu Kediri - Ratnasari, Desy Yulia; Susilaningsih, Nunung; Heryanto, Budi (Universitas Kadiri, 2023)
The main objective of this research is to determine the influence of Financial Compensation and Non-Financial Compensation on Employee Performance of PT Astra Internasional, Tbk-Daihatsu Kediri Employees. The type of research used in this research is explanatory research with a quantitative approach. The sample in the study consisted of 103 employees and was a saturated sample. Data analysis in this study used descriptive analysis and inferential statistical analysis. Based on the test results, it is proven that Financial Compensation has a significant effect on Employee Performance; this is indicated by a significant t of 0.046, which is smaller than 0.05. Non-financial compensation significantly affects employee performance; this is shown by a significant t of 0.049, which is smaller than 0.05.